Análisis de la estructura del plan de negocio para ‘Serendipia Wooman’ (2021)
This article analyzes the business plan structure for ‘Serendipia Wooman’, a Colombian venture that promotes learning environments for personal development, promoting female empowerment through selfknowledge processes by means of the Wooman methodology. The value proposition is mainly based, in this methodology, on selfknowledge ―physical, mental, emotional and existential― that integrates the different phases of the month through the feminine and lunar cycle, and that allows expressing the maximum personal potential, as well as visualizing better results in the different areas of life. On the other hand, it seeks the creation of a female community of empowerment, this, by hiring certified transformation agents with the profile to implement this methodology. ‘Serendipia Wooman’ seeks, initially, to have a positive impact on the quality of life of women living in Bogota between the ages of 20 and 40. The model has considered key factors such as macroeconomic variables that influence the projections; likewise, all the inputs required to develop a sales analysis in number of units and in money, sales costs and operating expenses have been taken into account, in order to obtain a clear income statement that shows the net profit. In addition, from the operating flow, it is sought to know the month in which the investment required for the beginning of the commercial activity can be recovered.